Odpowiedzi

2010-02-27T12:25:44+01:00
Z.13
d)
P = (1/3)*π *(6² - 3²) = (1/3)*π *(36 - 9) = (1/3)*27*π = 9π
e)
P = 2*(1/2)*π*5² + 2*(1/2)*π*3² = 25π + 9π = 34 π
f)
P =8² - (1/4)π*8² = 64 - (64/4)π = 64 - 16π
g)
P = (1/4)π*8² - (1/2)*8² = 16π -32 = 16*( π - 2)
h)
P =(1/2)*π*8² - 2*(1/2)*π*4² = 32 π - 16 π = 16 π
z.14
a)
L = 4*L1 +2*L2 +2 *L3
L1 = 4*(1/4)*2π*2 = 4π
L2 = 8
L3 = 5
L = 4*4π + 2*8 + 2*5 = 16 π +16 + 10 = 16 π + 26
Odp. L = 16 π + 26
b)
L = 2*(1/4)*2π*2 + 2*7 + 4 + (1/2)*2π*4 =
= 2 π + 14 + 4 + 4 π = 6 π + 18 = 6*( π + 3)